2021
DOI: 10.1093/nargab/lqab096
|View full text |Cite
|
Sign up to set email alerts
|

pLS20 is the archetype of a new family of conjugative plasmids harboured byBacillusspecies

Abstract: Conjugation plays important roles in genome plasticity, adaptation and evolution but is also the major horizontal gene-transfer route responsible for spreading toxin, virulence and antibiotic resistance genes. A better understanding of the conjugation process is required for developing drugs and strategies to impede the conjugation-mediated spread of these genes. So far, only a limited number of conjugative elements have been studied. For most of them, it is not known whether they represent a group of conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…One of these was based on the replication region and the other on a concatenated sequence of nine conserved orthologous genes. This analysis resulted in two very similar trees in which these plasmids were divided into four clades [11]. pLS20 belongs to clade I, together with 23 other plasmids, and p576 belongs to clade II, together with six other plasmids.…”
Section: Establishment Genes Present On Pls20 Family Plasmids Are Regulated By One Of the Two Different Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of these was based on the replication region and the other on a concatenated sequence of nine conserved orthologous genes. This analysis resulted in two very similar trees in which these plasmids were divided into four clades [11]. pLS20 belongs to clade I, together with 23 other plasmids, and p576 belongs to clade II, together with six other plasmids.…”
Section: Establishment Genes Present On Pls20 Family Plasmids Are Regulated By One Of the Two Different Mechanismsmentioning
confidence: 99%
“…In those cases where the plasmid sequence was present in the database as one large linear contig that probably corresponds to most of the plasmid sequence, the name was extended with a single dagger. Names are extended with a double dagger symbol when the plasmid was reconstructed form two or several contigs [11]. Putative establishment regulons of the other clade II plasmids are approximately aligned with that of p576.…”
Section: (Putative) Establishment Genes Regulated By Egers2mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that pLS20 is the prototype of a family of related plasmids and that the conjugation operons present on all these plasmids (i) contain multiple intrinsic terminators and (ii) start with a processive antitermination (P-AT) system, named conAn [ 30 , 31 ]. The conAn system contributes to the strictly controlled expression of the conjugation genes by minimizing the effects of spurious transcription and allowing the differential expression of subsets of genes within the conjugation operon.…”
Section: Introductionmentioning
confidence: 99%